The applicability of the proposed accreditation of external auditors of publicly listed companies and their additional reporting requirements - Castillo, Jhoanna Paula (Animo Repository, 2002)
This research paper aims to determine whether the proposed accreditation of external auditors of publicly listed companies and their additional reporting requirements applicable in the Philippines or not. It determines the reasons on why the SEC proposed such amendments as well as the criteria used in deriving the qualifications from publicly listed companies and from the external auditors are gathered and analyzed. Increase in number of fraud cases and changes in international standards are primary reason that made SEC proposed such accreditation. The BSP criteria for accreditation and its imposed additional reporting requirements and the reactions from external auditors are considered in deriving the criteria for accreditation. Most of the publicly listed companies welcome the accreditation since they believe it is beneficial to them. A more quality audit reports will be presented to the public. However, external auditors commented that such accreditation would mean work on their part and could affect the relationship of the cleint with its external auditor."